APT Winnti Panda as a Power-Gathering Tool in International Cyberspace - Septiasari, Rycka; Kurniawan, Yandry; Arifandy, Mohamad; Putri, Erika Husna Nabila (AI Society & STMIK Indonesia, 2025)
This study provides an analysis of the Advanced Persistent Threat (APT) Winnti Panda impact on Indonesian infrastructure in 2022, which is a tool for gathering power in international cyberspace. The cybersecurity dilemma concept is utilized to explain the phenomena that occur using a deductive qualitative method. This study highlights how Indonesia perceives the cyber threats posed by the APT Winnti Panda. The data used in this study are primary data sourced from the Indonesian Cyber Security Agency (BSSN), which was taken through interviews. In addition, secondary data is also used using the archival and desk research methods from various online and offline sources. The main argument of this study is that the APT Winnti Panda, which attacked Indonesia in 2022, is a tool used to gather power in international cyberspace.